2010
DOI: 10.1111/j.1365-2044.2010.06561.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of mirtazapine in preventing intrathecalmorphine‐induced nausea and vomiting after orthopaedic surgery*

Abstract: SummaryNausea and vomiting are frequent complications of intrathecal morphine. In this randomised, double-blind trial, we tested the efficacy of mirtazapine, an antidepressant that blocks receptors associated with vomiting, on the incidence of nausea and vomiting after intrathecal morphine. One hundred patients receiving spinal anaesthesia for lower limb surgery were assigned equally to take either an orally disintegrating form of 30 mg mirtazapine or matching placebo 1 h before surgery. Spinal anaesthesia was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 28 publications
3
14
0
Order By: Relevance
“…Previous studies suggested other types of antiemetic drugs such as mirtazapine, 5-HT 3 receptor blockers, and antihistaminic might be effective for prevention of opioid-induced nausea. [22][23][24][25] In our study, steroids were used not only to prevent opioid-induced nausea or vomiting, but also to improve well-being (betamethasone 1-4 mg/d). Further studies will be needed in this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested other types of antiemetic drugs such as mirtazapine, 5-HT 3 receptor blockers, and antihistaminic might be effective for prevention of opioid-induced nausea. [22][23][24][25] In our study, steroids were used not only to prevent opioid-induced nausea or vomiting, but also to improve well-being (betamethasone 1-4 mg/d). Further studies will be needed in this issue.…”
Section: Discussionmentioning
confidence: 99%
“…Momentum is gaining for the use of mirtazapine in several clinically relevant aspects of opioids, including opioid-mediated antinociception (Milne, Sutak, Cahill, and Jhamandas, 2008;Schreiber, Rigai, Katz, and Pick, 2002;Sikka, Kaushik, Kumar, Kapoor, Bindra, and Saxena, 2011) and acute tolerance to this effect (Milne, Sutak, Cahill, and Jhamandas, 2008), nausea and vomiting (Chang, Ho, and Sheen, 2010), as well as reward, physical dependence and withdrawal associated with repeated opioid treatments (Kang, Wang, Li, Hu, Zhang, and Li, 2008). Toward the goal of characterizing the potential for addiction therapy, we explored the utility of mirtazapine to mitigate previously established cellular (McDaid, Tedford, Mackie, Dallimore, Mickiewicz, Shen, Angle, and Napier, 2007) and behavioral (Graves and Napier, 2011;Herrold, Shen, Graham, Harper, Specio, Tedford, and Napier, 2009;McDaid, Tedford, Mackie, Dallimore, Mickiewicz, Shen, Angle, and Napier, 2007;Voigt, Mickiewicz, and Napier, 2011) consequences of abused drugs, with a focus on methamphetamine.…”
Section: Introductionmentioning
confidence: 99%
“…However, most major orthopedic surgery like THR and TKR involves large injured tissues and requires much time under general or regional anesthesia. As a result, there are potential risks of many unpleasant symptoms which may affect patients, including physiological, psychological, and social symptoms, such as pain, distress, anxiety, fatigue, discomfort, sleep disturbance, nausea, vomiting, and so on [27,28,29] . The current study tries to describe and compare between physical health problems following THR and TKR surgeries.…”
Section: Discussionmentioning
confidence: 99%